The role of hospital school education in reducing anxiety among hospitalized children - Padillo-Andicoberry, Ana; de Asís Díaz-Beato, Francisco; Sánchez-Lissen, Encarnación; Romero-Pérez, Clara (Frontiers in Education, 2025)
PurposeThis study aimed to evaluate state and trait anxiety levels in hospitalized children upon admission and discharge from the HS, and to examine whether curriculum-based activities and illness-related factors influence anxiety evolution.DesignA prospective pretest-posttest design without a control group was conducted in a hospital school setting. Sixty children aged 9 to 14 completed the State–Trait Anxiety Inventory for Children (STAIC) at admission and before discharge. An adapted Likert-based visual scale was used to assess satisfaction with educational activities. Additional variables included type of illness and treatment, length of stay, and previous hospitalizations.FindingsChildren exhibited significantly higher state anxiety compared to trait anxiety upon admission (53rd vs. 31st percentile; p = 0.001). Previous hospitalization was a strong predictor of elevated state anxiety (p = 0.008). Both trait and state anxiety significantly decreased following hospital school attendance (p = 0.007; p = 0.001, respectively). A longer hospital school attendance (>6 days) was associated with a greater reduction in trait anxiety (p = 0.035). Positive evaluation of educational activities predicted a favorable anxiety evolution (AUC = 0.815; p = 0.004).ValueThis study highlights the protective role of hospital school interventions in mitigating anxiety among hospitalized children. Previous admissions emerged as a significant risk factor, while high satisfaction with educational activities correlated with improved emotional outcomes. Visual satisfaction scales may serve as practical tools to identify children at risk of heightened anxiety during hospitalization.